Pemberdayaan Perempuan Pedesaan Melalui Optimalisasi Kreativitas Berbasis Produk Unggulan Bambu Sebagai Upaya Peningkatan Perekonomian Keluarga - Zahara, Vadilla Mutia; Ginanjar, Rah Adi Fahmi; Suci, Stannia Cahaya; Anwar, Cep Jandi; Herlina, Deswita (Universitas Nusantara PGRI Kediri, 2022)
According to the BKKBN, family welfare indicators can meet basic needs such as food, clothing, and housing. Currently, it is not only men who play a role in the family economy, but women also have a role in helping to improve the family's economy. Especially during Covid-19 where the average family income has decreased. The purpose of this service is to optimize the creation of village women through the use and innovation of superior bamboo products as a way to take part in improving the family economy. This service is carried out in the target village located in Pasuluhan Village, Walantaka District, Serang Banten. The method of implementing this service is carried out by conducting counseling with community development in a persuasive and educative manner and mapping participants regarding the business interests of village women, including women and youth groups. The results of the implementation of this service include the innovation of bamboo products in Pasuluhan village, the positive response, and motivation of village women to become entrepreneurs according to their interests and expertise.